2022
DOI: 10.1088/1402-4896/ac60f5
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and structural characteristics of fish skin gelatin as alternative biopolymer electrolyte

Abstract: This article presented new sequences of fish gelatin (FG) as a polymer host for solid polymer electrolytes (SPEs) impregnated with ammonium nitrate (NH4NO3) and the impact of different amounts of salt on the properties of the formed electrolyte were investigated. X-ray diffraction (XRD) analysis revealed that the electrolyte containing 25 wt.% NH4NO3 salt to be the most amorphous in nature. Fourier transform infrared (FTIR) spectroscopy analysis showed that the peak of amide III shifted to a lower wavenumber a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Apart from the effect of ultrasonic waves on jellyfish collagen, the desalination effect of salted jellyfish by ultrasound also lowered the wavenumbers of the amide III band. Nadzrin et al [44] reported the effect of salt content on the amide III band. The H + of salt content can facilitate complexation with atoms in the amide III functional group, increasing ionic conductivities and lower wavenumber.…”
Section: Plos Onementioning
confidence: 99%
“…Apart from the effect of ultrasonic waves on jellyfish collagen, the desalination effect of salted jellyfish by ultrasound also lowered the wavenumbers of the amide III band. Nadzrin et al [44] reported the effect of salt content on the amide III band. The H + of salt content can facilitate complexation with atoms in the amide III functional group, increasing ionic conductivities and lower wavenumber.…”
Section: Plos Onementioning
confidence: 99%